Incorporating Inter-System Bias in Single Point Positioning Based on GPS, Galileo and BeiDou System - Kwaśniak, Dawid Łukasz; Cellmer, Sławomir (Geomatics and Environmental Engineering, 2021)
The increasing number of satellites provides new opportunities. In the experiment presented in this paper, the Single Point Positioning technique is tested. Data from four different receivers were used in the tests. The GPS, Galileo and BeiDou System observations were collected over a three day long observational session. The computational process was carried out using self‑made software and point positions were obtained as the result. The goal of the test was to verify the impact of the Inter‑System Bias (ISB) on the final results. For this purpose, two cases of processing data were compared: with estimating ISB and without taking into account this parameter. In the paper the formulas of the mathematical models used are presented and, in both of the considered cases, a combination of GPS, BDS and Galileo was used. The results show that in the case where the ISB was taken into account, the accuracy and precision in the positioning was much better than in the approach where the ISB was not considered. Estimating the ISB allows for more precise positioning results to be obtained for car-navigation or GIS purposes.